Conducting an ongoing HIV clinical trial during the COVID-19 pandemic in Uganda: a qualitative study of research team and participants' experiences and lessons learnt. Issue 4 (21st April 2021) - Muwanguzi, Patience A; Kutyabami, Paul; Osingada, Charles Peter; Nasuuna, Esther M; Kitutu, Freddy Eric; Ngabirano, Tom Denis; Nankumbi, Joyce; Muhindo, Richard; Kabiri, Lydia; Namutebi, Mariam; Nabunya, Racheal; Kiwanuka, Noah; et al.
Abstract : Objective: To explore the experiences and lessons learnt by the study team and participants of the Workplace-based HIV self-testing among Men trial during the COVID-19 pandemic in Uganda. Design: An explorative qualitative study comprising two virtual focus group discussions (FGDs) with 12 trial team members and 32 in-depth participant interviews (N=44). Data were collected via telephone calls for in-depth interviews or Zoom for FGDs and manually analysed by inductive content analysis. Setting: Fourteen private security companies in two Uganda districts. Participants: Members of the clinical trial study team, and men working in private security companies who undertook workplace-based HIV testing. Results: The key themes for participants experiences were: 'challenges in accessing HIV treatment and care, and prevention services', 'misinformation' and 'difficulty participating in research activities'. The effects on HIV treatment and prevention resulted from; repercussions of the COVID-19 restrictions, participants fear of coinfection and negative experiences at health facilities. The difficulty in participating in research activities arose from: fear of infection with COVID-19 for the participants who tested HIV negative, transport difficulties, limited post-test psychosocial support and lack of support to initiate pre-exposure prophylaxis. The key study team reflections focused on the management of the clinical trial, effects of the local regulations and government policies and the need to adhere to ethical principles of research. Conclusions: Findings highlight the need to organise different forms of HIV support for persons living with HIV during a pandemic. Additionally, the national research regulators and ethics committees or review boards are strongly urged to develop policies and guidelines for the continuity of research and clinical trials in the event of future shocks. Furthermore, this study calls on the appropriate government agencies to ensure public and researchers' preparedness through continuing education and support. Trial registration number: Clinicaltrials.gov NCT04164433 ; Pre-results.